Metode Penemuan (Inquiry) Untuk Meningkatkan Pemahaman Siswa Dalam Mata Pelajaran Matematika - Warpaatun Warpaatun (Jurnal Bintang Pendidikan Indonesia, 2023)
The world of education in the 21st century faces formidable challenges, especially in the fields of science and technology which are very rapid. Changes in world society and our own society in the socio-cultural field and the growing issue that the quality of education is low. Therefore, to face these challenges, education and learning requires changes in both quantity and quality. Various efforts have been made in the field of education. Teachers as direct executors of achieving learning objectives need to improve the quality of the learning process by paying attention to how to convey the knowledge they have to their students. The discovery method in learning mathematics is intended to encourage students to understand something that is factual or mathematical relations that are still new to students, for example certain patterns, characteristics or formulas. After finding facts/relations students are asked to draw a generation from what they find. The Inquiry method is a method that can lead students to realize what they have learned while studying. Inquiry places students as active learning subjects. So learning mathematics using the discovery method (inquiry) can increase student understanding.